Plan de desarrollo que promueva el turismo en la parroquia San Isidro cantón Sucre - Faubla Cuzme, María José (2015)
The objetive of the research was to design a development plan to promote tourism and to improve the quality of life of the population, to increase sustainable tourism in the San Isidro Parish of Sucre Canton. The research was quantitative and qualitative, is based on literature review, field observation and establishing procedures and strategies. A methodological procedure was divided into three stages: initial diagnosis, market research and preparation of the development plan. The baseline was supported with geographic, political, environmental, social, economical and tourism data, as well as the characterization of tourism resources of the parish. The supply and demand in which tools such as SWOT matrix was used. An expert consultation was performed to determine the projects that were included in the development plan. A development plan was structured with a total of eight programs and eleven projects based on the PLANDETUR 2020, as well as the National Plan for Good Living 2013 - 2017. The investigation showed that San Isidro parish has natural and cultural tourism resources, including archaeological sites, as well as human talent available to train and work for the welfare of the parish, factors that are taxed to implement a development plan to promote tourism and social and economical development for the community.